2001
DOI: 10.1017/s1481803500005534
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent bleeding in acute upper gastrointestinal hemorrhage: transfusion confusion

Abstract: Objective: Acute upper gastrointestinal (UGI) hemorrhage is a common, often serious condition encountered in the emergency department (ED). Previous research has suggested that transfusion of blood products may interfere with the hypercoagulable state induced by significant blood loss. Our objective was to determine whether the frequency of rebleeding is higher in patients with UGI bleeding who have received early blood transfusion. Methods: The study was a retrospective chart review of patients admitted to ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…In a study done by Jeffery it is found that the outcome of transfused patients was significantly worse than that of nontransfused patients. [4] In a study done by Schiller et al patients given a transfusion of not more than 4 bottles had a low fatality rate which was similar to that of those who were not transfused. Patients receiving 5-10 bottles of blood had double this fatality rate.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…In a study done by Jeffery it is found that the outcome of transfused patients was significantly worse than that of nontransfused patients. [4] In a study done by Schiller et al patients given a transfusion of not more than 4 bottles had a low fatality rate which was similar to that of those who were not transfused. Patients receiving 5-10 bottles of blood had double this fatality rate.…”
Section: Discussionmentioning
confidence: 87%
“…Patients can be stratified as having either variceal or nonvariceal sources of upper GI hemorrhage as the two have different treatment algorithms and prognosis. [4] The primary diagnostic test for evaluation of UGIB is endoscopy. Early endoscopy and endoscopic appearance of certain lesions helps to guide care and thereby reduce the costs and duration…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Patients can be divided as having either variceal or nonvariceal sources of upper GI hemorrhage as the two have different management protocols and prognosis. 6 The primary diagnostic test for evaluation of upper GI bleeding is endoscopy. Endoscopy for upper GI bleed has a sensitivity of 92%-98% and specificity of 30%-100%.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 With the increasing incidence of use of NSAIDS in the elderly, the pateints presenting the above cause in about two third the population also due to high prevelance to comorbid conditions (like cardiovascular disease) 5,7 Patients with upper GI bleed can be divided into variceal and non variceal sources of bleed each have different protocols of management and prognosis. 6 The first and the most common cause is portal hypertension resulting in gastroesophageal varices and portal hypertensive gastropathy, second most common cause being peptic ulcer disease, other causes include erosive gastritis, reflux esophagitis, Mallory weiss tear, malignancy etc. Patients with age more than 60 years had mortality rates ranging from 12-35%, patients with age less than 60 years was <10% and overall mortality rates of 5-11%, as noted in previous studies.…”
Section: Introductionmentioning
confidence: 99%